Productivity, wages and relationships - Gylfi Zoega (University of Iceland, Institute of Economic Studies (IoES), 2008)
Labour demand and wages depend on the state and volatility of relationships within firms. Good relationships lower profit-maximising wages and raise firms' profits and hence constitute an asset to the firm. Wages are lower because when people enjoy collaborating in the absence of wage incentives it is costly to induce them to work even more using such incentives due to rising marginal disutility of effort. Perhaps more surprisingly, volatile relationships among workers who collaborate raise profits and the value of workers in the presence of increasing returns to labour. Such volatility has the effect of raising the profitmaximising wage.
Keywords: 330; labor demand; human capital; wage level; Work atmosphere; corporate success; Arbeitsnachfrage; Humankapital; Lohnniveau; Betriebsklima; Unternehmenserfolg; Theorie